Alih Kode dalam Film Winter Elegy - Nafisah, Putri Kholifatun; Al Fatah, M. Yanuar; Azalia, Rifdah; Puspita, Ina Deby; Wildana, Amran Roky; Madjid , Natasya Hidayati (DESANTA (Indonesian of Interdisciplinary Journal), 2024)
This study aims to identify and describe the functions of code switching that occur in conversations between characters in the film, which consists of three main functions, namely respecting the interlocutor, familiarizing the atmosphere, and telling secrets. This research uses descriptive qualitative method by collecting data from the dialog in the film uploaded on YouTube, as well as observing and recording conversations that show code switching. The results show that code-switching in this movie functions as a way to show respect, create intimacy, and keep and reveal secrets between characters. The findings emphasize the importance of code-switching in cross-cultural and linguistic communication, which plays a role in strengthening social relationships and adjusting to the cultural background of the interlocutor.